Bakteri halofilik dan halotoleran dari air baku tambak garam Universitas Trunojoyo Madura: Halophilic and halotolerant bacteria from raw water of salt ponds of Trunojoyo University Madura - Salsabil Firda Nazhifan; Kartika Dewi; Eka Nurrahema Ning Asih (Jurnal Pengolahan Hasil Perikanan Indonesia, 2023)
Halophiles are bacteria that require specific salt concentrations to survive, while halotolerants are bacteria that grow in the absence of salt and in the presence of high salt concentrations. Both halophiles and halotolerant bacteria have potential biotechnological applications. The aim of this study was to isolate moderate halophiles and halotolerant bacteria from the raw water of salt ponds at Trunojoyo Madura University and to determine their morphological and biochemical characteristics. Four halophilic bacterial isolates with codes AB.1.2, AB.2.4, AB.2.5, and AB.3.6, and two isolates of halotolerant bacteria with codes AB.1.1 and AB.2.3, were obtained. All isolates were coccus shaped, and most of the isolates were gram-negative. Three isolates were identified as aerobic bacteria based on catalase and oxidase tests. Only halotolerant bacteria AB.1.1 and AB.2.3, showed positive results in the citrate utilization test, while halophiles AB1.2, AB.2.5, and AB.3.6, showed positive results in the urease test. All isolates, both halophiles and halotolerant, were able to utilize sucrose, glucose, mannitol, and maltose.